The Effect of Discipline and Work Environment on Employee Performance in Ciputat Sector Police - Rima Handayani (PINISI Discretion Review, 2019)
Human Resources (HR) is very important to be able to carry out the role of tasks, operationalize the available technology and provide innovative and creative thinking. The purpose of this study was to determine how the Effect of Discipline and Work Environment on Employee Performance in Ciputat Sector Police, where the independent variables studied were Discipline (X1) and Work Environment (X2), while the dependent variable was Employee Performance (Y). This method uses a quantitative approach, with the nature of descriptive associative research. The statistical tool used in the form of multiple linear regression, and carried out through the SPSS program 20 populations taken were Ciputat Sector Police officers as many as 108 people and the sample technique used was using the Slovin formula so that the number of respondents sampled was 52 people. In testing the hypothesis the author uses the t test for partial hypotheses and the f test for simultaneous hypotheses. Based on partial hypothesis testing using the f test and t test where the test results show that the fcount is 201.736> and f table is 3.190 which means the independent variable (X) has an influence on employee performance while the results of the t test results in disciplinary variables produce t arithmetic 4,613> and t table 2,009 which means tcount> ttable and work environment variables produce t arithmetic of 6.353> and t table of 2.009 which means tcount> with a contribution value of 89.2% which means that the contribution of the Disciplinary variable ( X1) and Work Environment (X2) affect the variable Y (Employee Performance) that is equal to 89.2% while the remaining 10.8% variable Y (Employee Performance) is influenced by other factors not examined by the author.